Models, Mindsets, Meta : The What, the How, and the Why Not? : Essays Dedicated to Bernhard Steffen on the Occasion of His 60th Birthday /: The What, the How, and the Why Not? : Essays Dedicated to Bernhard Steffen on the Occasion of His 60th Birthday. ([2019]) - Unknown
No abstract available